2019
DOI: 10.18632/oncotarget.26699
|View full text |Cite
|
Sign up to set email alerts
|

HIGH expression of OSM and IL-6 are associated with decreased breast cancer survival: synergistic induction of IL-6 secretion by OSM and IL-1β

Abstract: Chronic inflammation has been recognized as a risk factor for the development and maintenance of malignant disease. Cytokines such as interleukin-6 (IL-6), oncostatin M (OSM), and interleukin-1 beta (IL-1β) promote the development of both acute and chronic inflammation while promoting in vitro metrics of breast cancer metastasis. However, anti-IL-6 and anti-IL-1β therapeutics have not yielded significant results against solid tumors in clinical trials. Here we show that these three cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 77 publications
3
53
0
Order By: Relevance
“…OSM (oncostatin M) was involved in tumor development and insulin resistance [43]. It has been reported that OSM as a risk factor promote breast cancer metastasis [44]. Studies indicated that the expression of NR2F2 (Nuclear receptor subfamily 2) are associated with survival outcome in gastric cancer [45] and breast cancer [46].…”
Section: Discussionmentioning
confidence: 99%
“…OSM (oncostatin M) was involved in tumor development and insulin resistance [43]. It has been reported that OSM as a risk factor promote breast cancer metastasis [44]. Studies indicated that the expression of NR2F2 (Nuclear receptor subfamily 2) are associated with survival outcome in gastric cancer [45] and breast cancer [46].…”
Section: Discussionmentioning
confidence: 99%
“…2. A member of the IL-6 family of cytokines, Oncostatin M (OSM) can induce IL-6 upregulation and STAT3 phosphorylation to promote breast cancer progression [13] and to activate STAT3 and hypoxia inducible factor 1 alpha (HIF-1α) in estrogen receptor (ER)-breast cancer cells or in ER+ breast cancer cells in cooperation with IL-6 [14]. Additionally, other interleukins, such as IL-35 and IL-8, are also found to promote breast cancer progression by activating STAT3.…”
Section: Advances In the Study Of Stat3 Signaling Pathways In Breast mentioning
confidence: 99%
“…In the presence of OSM, T47D cells exhibited decreased intercellular contact [122], and increased cellular detachment and invasiveness [123]. In patient data, high OSM expression has also been correlated with decreased patient survival, pointing to its possible role in metastatic disease [124]. In the context of breast cancer bone metastasis, one group has shown that OSM knockdown in 4T1 mouse mammary carcinoma cells reduced spontaneous metastasis to the spine, as assessed by qPCR analysis following orthotopic injections, and less osteolytic bone destruction following intratibial injections [125].…”
Section: Gp130 Cytokines In Breast Cancermentioning
confidence: 98%
“…Activation of downstream signaling by the gp130 family: Upon binding to gp130 and their cytokine-specific receptor on tumor cells, the gp130 ligands are known to activate the JAK/STAT, MAPK/MEK/ERK, and PI3K/AKT signaling pathways [20][21][22][23]. While there has not been a comprehensive comparison of the downstream pathways activated by each ligand in breast cancer, many mechanistic studies have identified STAT3 as the key downstream mediator of IL-6 [127] and OSM [124,128,129] tumor-promoting effects. Signal transduction by IL-6, LIF, and OSM is initiated after dimer formation between the cytokine specific receptors (e.g., IL-6R, LIFR, and OSMR) and gp130, resulting in the phosphorylation of STAT3 by JAK [16,130,131].…”
Section: Gp130 Cytokines In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation